Regional differences in heart failure risk in the United Kingdom are partially explained by biological aging - Wong, Jason Y. Y.; Blechter, Batel; Rodriquez, Erik J.; Shearer, Joseph J.; Breeze, Charles; Pérez-Stable, Eliseo J.; Roger, Véronique L. (Frontiers in Public Health, 2024)
Background: Heart failure (HF) risk is greater in rural versus urban regions in the United States (US), potentially due to differences in healthcare coverage and access. Whether this excess risk applies to countries with universal healthcare is unclear and the underlying biological mechanisms are unknown. In the prospective United Kingdom (UK) Biobank, we investigated urban-rural regional differences in HF risk and the mechanistic role of biological aging.Methods: Multivariable Cox regression was used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of incident HF in relation to residential urban-rural region and a Biological Health Score (BHS) that reflects biological aging from environmental, social, or dietary stressors. We estimated the proportion of the total effect of urban-rural region on HF mediated through BHS.Results: Among 417,441 European participants, 10,332 incident HF cases were diagnosed during the follow-up. Compared to participants in large urban regions of Scotland, those in England/Wales had significantly increased HF risk (smaller urban: HR=1.83, 95%CI: 1.64-2.03; suburban: HR=1.77, 95%CI: 1.56-2.01; very rural: HR=1.61, 95%CI: 1.39-1.85). Additionally, we found a dose-response relationship between increased biological aging and HF risk (HRper 1 SD increase=1.14 (95%CI: 1.12-1.17). Increased biological aging mediated a notable 6.6% (p<0.001) of the total effect of urban-rural region on HF.Conclusions: Despite universal healthcare in the UK, disparities in HF risk by region were observed and may be partly explained by environmental, social, or dietary factors related to biological aging. Our study contributes to precision public health by informing potential biological targets for intervention.